Wildfire risks under a changing climate: Synthesized assessments of wildfire risks over southwestern China - Xu, Yuanxin; Guo, Haiyan; Liu, Jia; Sun, Rui; Li, Xiaolan (Frontiers in Environmental Science, 2023)
Wildfire events in the southwestern China resulting in catastrophic loss of property and human life, and the localized wildfire risks show differentiated trends under warming scenarios. In case of quantitating climate impacts and localizing wildfire risks, synthesized assessments of wildfire risks of high-incident areas in the southwestern China are established and mapped in this article, which are constituted by three basic elements: hazard, vulnerability and disaster prevention/mitigation capacity. Vegetation ignitability and fire spreading related climate and topography factors are selected and interpolated as the hazard part, public and economic characteristic elements are grouped into vulnerability and disaster prevention/mitigation capacity based on their functions and influences with wildfire events, each factors and groups are rated by the historical wildfire site records and weighted by entropy weight method and analytic hierarchy process. Assessments indicates that most very high wildfire risk girds distribute in the west of 103°E and the north of 28°N, cover an area of over 26500 km2, mainly occur in low altitude suburban regions in basins and valleys with high climate hazards. The highly localized wildfire risk maps specified both stresses of fire prevention/mitigation in each grid cells and general spatial patterns of wildfire risks, therefore enhance the understanding of both current and future patterns of wildfire risks, and thus help improve suppression and prevention policies.